Concurrent Engineering of Tolerance Synthesis and Process Selection for Products with Multiple Quality Characteristcs Considering Process Capability - Mustajib, Mohamad Imron (UI Scholars Hub, 2012)
The existences of variances that are very difficult to be removed from manufacturing processes provide significance of tolerance to the product quality characteristics target of customer functional requirement. Furthermore, quality loss incurred due to deviation of quality characteristics of the target with a specified tolerance. This article discusses the development of concurrent engineering optimization model of tolerance design and manufacturing process selection on product with multiple quality characteristics by minimizing total costs in the system, namely total manufacturing cost and quality loss cost as functions of tolerance, also rework and scrap costs. The considered multiple quality characteristics have interrelated tolerance chain. The formulation of proposed model is using mixed integer non linear programming as the method of solution finding. In order to validate of the model, this study presents a numerical example. It was found that optimal solution are achieved from proposed model in the numerical example.